Management for a Rare Occurrence of Low Grade Endometrial Stromal Sarcoma (LGESS): A Case Report and Literature Review - Rakesh, Dr. Amrita; Singh, Dr. Pritanjali; Shankar, Dr. Abhishek; Ranjan, Dr. Rakesh (International Journal of Innovative Research in Medical Science, 2022)
According to the American Cancer Society 2017 facts and figures, an estimated 4910 cases of uterine sarcomas are anticipated. According to a population-based analysis from 1988-2003, the overall incidence of ESS among all the uterine malignancies is only 0.2-1%, making it a rather rarer subtype of uterine sarcomas. The median age was 52 years (range: 17-96 years). Surgical treatment was associated with better survival outcomes than other therapy, and especially followed by adjuvant therapy of hormone treatment should be offered, especially in recurrent cases of LGESS. Due to paucity of understanding on the management of this rarer subtype of uterine sarcoma, a case report with review of literature is done which suggests that after surgical debulking, starting patients of maintenance hormonal treatment is the best approach as per current scenario.